Energy Level Alignment at Metal/Solution‐Processed Organic Semiconductor Interfaces. Issue 19 (15th March 2017) - Atxabal, Ainhoa; Braun, Slawomir; Arnold, Thorsten; Sun, Xiangnan; Parui, Subir; Liu, Xianjie; Gozalvez, Cristian; Llopis, Roger; Mateo‐Alonso, Aurelio; Casanova, Felix; Ortmann, Frank; Fahlman, Mats; et al.
Abstract : Energy barriers between the metal Fermi energy and the molecular levels of organic semiconductor devoted to charge transport play a fundamental role in the performance of organic electronic devices. Typically, techniques such as electron photoemission spectroscopy, Kelvin probe measurements, and in‐device hot‐electron spectroscopy have been applied to study these interfacial energy barriers. However, so far there has not been any direct method available for the determination of energy barriers at metal interfaces with n‐type polymeric semiconductors. This study measures and compares metal/solution‐processed electron‐transporting polymer interface energy barriers by in‐device hot‐electron spectroscopy and ultraviolet photoemission spectroscopy. It not only demonstrates in‐device hot‐electron spectroscopy as a direct and reliable technique for these studies but also brings it closer to technological applications by working ex situ under ambient conditions. Moreover, this study determines that the contamination layer coming from air exposure does not play any significant role on the energy barrier alignment for charge transport. The theoretical model developed for this work confirms all the experimental observations. Abstract : In‐device hot‐electron spectroscopy is demonstrated as a direct and reliable technique for the determination of the energy barrier between a metal and a solution‐processed electron‐transporting organic semiconductor. With experimental advance, this work opens new possibilities to bring this technique closer to the organic electronics industry.